PENGARUH PENGGUNAAN PAKAN TOTAL MIXED RATION TERHADAP KONSUMSI DAN NILAI EKONOMIS PAKAN PADA SAPI PERAH: The Effect of Total Mixed Ration Feeding on The Consumption and Economic Value of Feed in Dairy Cows - Bima Kusuma; Usman Ali; umi kalsum (Departemen Nutrisi dan Makanan Ternak, Fakultas Peternakan, Universitas Hasanuddin, 2021)
The study aims to analyze the effect of Total Mixed Ration feeding on the consumption and economic value of feed in dairy cows. This research material is 9 PFH lactation dairy cows that an average milk production of 10 liters /head/day. Concentrate feed and forage of maize stover, as well as supporting tools such as cash machines, test tubes, and lactoscan. This study uses Complete Randomized Design (CRD) covering 3 feed treatments of concentrate used in feed Total Mixed Ration(TMR), P1 = concentrate 20% of the needs of DM feed, P2 = concentrate 30% of the needs of DM feed, and P3 = concentrate 40% of the needs of DM feed-in TMR feed, Variety analysis continued SRD test. The results showed that the uses of concentrates in TMR feed had an unreal effect (P>0.05) on dry material consumption (DMC) and organic matter consumption (OMC) with an average DMC (kg/head/day) at P1 = 11,553, P2 = 12,627, P3 = 12,760. Organic Material Consumption (kg/head/day) at P1 = 8,887, P2 = 10,467, and P3 = 10,833. However, has a significant effect (P<0.05) on the economic value of feed. It can be concluded that the greater level of concentrate use in TMR feed has no effect on DMC and OMC and decrease the economic value of feed. The level of concentrate used of 40% resulted in the highest DMC value as big as 12,760 kg/head/day, and the highest OMC value of 10,833 kg/head/day, and the lowest economic value at Rp 21,412.67.